The efficacy and safety of aripiprazole for tic disorders in children and adolescents: A systematic review and meta-analysis. (August 2017) - Wang, Shuai; Wei, Yan-Zhao; Yang, Jian-Hong; Zhou, Yu-Ming; Cheng, Yu-Hang; Yang, Chao; Zheng, Yi
Abstract: The aims are to evaluate the efficacy and safety of aripiprazole for tic disorders (TDs) in children and adolescents. We searched PubMed, Embase, PsychINFO, Cochrane database as well as Chinese databases of CNKI, VIP, CBM and Wanfang from the database inception to October 2016, and 17 full-text studies (N=1305) were included in our article. The meta-analysis of 10 studies (N=817) showed that there was no significant difference in the reduction of total YGTSS score between aripiprazole and other drugs, and meta-analysis of 7 studies (n=324) which used tic symptom control ≧30% as outcome measure showed that there was no significant difference between aripiprazole and other treatments. The most common AEs of aripiprazole were the drowsiness, nausea/vomiting and increased appetite, and meta analysis which used the TESS scale as the outcome measurement showed that there was a significant difference between aripiprazole and haloperidol. In conclusion, these data provide moderate quality evidence that aripiprazole could be an effective and safe treatment option for TDs, and results from further trials are urgently needed to extend this evidence base. Highlights: We searched PubMed, Embase, PsychINFO, Cochrane database as well as Chinese databases of CNKI, VIP, CBM and Wanfang from the database inception to October 2016, and 17 full-text studies (N=1305) were included in our article. The meta-analysis of 10 studies (N=817) showed that there was no significant difference in the reduction of total YGTSS score between aripiprazole and other drugs. Meta analysis which used the TESS scale as the outcome measurement showed that there was a significant difference between aripiprazole and haloperidol. The most common AEs of aripiprazole were the drowsiness, nausea/vomiting and increased appetite. Aripiprazole shows therapeutic effectiveness and well tolerability in children and adolescents, and it could be considered as an alternative treatment option for tic disorders.